Finite element analysis of mandibular fracture fixation authenticated by 3D printed mandible mechanical testing - Omid Daqiq; Baucke van Minnen; Frederik Karst Lucien Spijkervet; Friederik Wilhelm Wubs; Gerton Lunter; Charlotte Christina Roossien (Scientific Reports)
Abstract Finite element analysis (FEA) for mandibular fracture fixation in craniomaxillofacial surgery remains promising but has been restricted due to the absence of an authenticated FEA model. This study aims to create an authenticated FEA model. This model was verified through a series of 3D printed mandible mechanical testing (3D-MMT) in a universal tensile machine using an indistinguishable set-up. Non-comminuted mandibular symphysis, parasymphysis, and angle fracture fixation stability were evaluated using a 2.0 mm 4-hole miniplate in three different plate configurations. Both FEA and 3D-MMT outcomes were reproducible and in agreement with the present understanding of stable mandibular fracture treatment. The results show favourable fracture stability with the dual plating, followed by the superior border, with the least stability observed in the inferior border plating. Furthermore, the FEA and the 3D-MMT outcomes were consistently similar, with a systematic 0.56 ± 0.12 mm total displacement difference (standard deviation). An excellent interclass relation coefficient (0.93, 95% confidence interval: 0.80–0.96) was found between the FEA model and the 3D-MMT mechanical test, indicating that both results were consistent with each other. The authenticated FEA can accurately study the recognised biomechanical behaviour of non-comminuted mandibular fractures and shows a potential application for complex fracture fixation analysis.